SAT-LB017 Anthropometric Imaging and Biological Markers of Adiposity and Aldosterone among African Americans: The Jackson Heart Study - Lee, Grace (J Endocr Soc, 2019)
Serum aldosterone increases risk of cardiometabolic disease. Pre-clinical studies suggest adipocytes produce aldosterone, independent of adrenal synthesis. Human studies have linked obesity and aldosterone, but mixed results exist between body fat distribution and aldosterone (1, 2). Body fat distribution varies by race with African Americans (AAs) having more subcutaneous adipose tissue (SAT) than visceral adipose tissue (VAT) compared to whites adjusted for total body fat (3). Thus, we examined the association of anthropometric, imaging and biological markers of adiposity with aldosterone among AAs. We used data from Exams 1 (2000-2004) and 2 (2005-2008) of the Jackson Heart Study, a large prospective study of AA adults. Descriptive statistics were obtained for demographic and clinical characteristics including mean and standard deviation (SD) for the continuous variables and frequencies for the categorical variables. Aldosterone, adiponectin, and leptin were log-transformed due to skewed distribution. Multivariable linear regression models were used to assess the associations of adiposity markers at Exam 1 (body mass index [(BMI]), waist circumference [(WC)], waist-to-height ratio [(WHR)], leptin, adiponectin) and at Exam 2 (VAT, SAT and liver attenuation [liver fat]) with aldosterone levels assessed at Exam 1. Models were adjusted for age, sex, education, occupation, systolic blood pressure, smoking and physical activity. Among 4994 adults (mean age 55.1 years ± 12.8, 63% female), the average BMI was 31.8 ± 7.3 kg/m(2). After full adjustment, a 1 unit increase in WC (cm) and BMI (kg/m(2)) were associated with a 0.5% and 0.8% higher aldosterone, respectively (both p<0.01). A 1% increase in adiponectin was associated with a 0.15% lower aldosterone (p<0.01); whereas, a 1% increase in leptin was associated with a 0.15% higher aldosterone (p<0.01). Compared to the highest BMI category (≥30 kg/m(2)), the 25-30 and <25 categories showed a 7.2% and 19% lower aldosterone, respectively (both p<0.01). A 1% increase in VAT was associated with a 0.18% increase in aldosterone and a 1% increase in liver attenuation was associated with a 0.34% decrease in aldosterone (both p<0.01), but no significant association was found with SAT. In conclusion, anthropometric measures of obesity, VAT and leptin were positively associated with serum aldosterone, while adiponectin and liver attenuation were negatively associated with serum aldosterone. These data suggest that adiposity may play a role in aldosterone levels among AAs. 1. O’Seaghdha et al, BMC Endocr Disord 12: 3, 2012; 2. Harada et al, Clin. Endocrinol. (Oxf.) 79, 510-516 (2013); 3. Katzmarzyk, et al. Am. J. Clin. Nutr. 91, 7-15 (2010). Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.